Study on the inhibitory effects and mechanisms of four polyphenolic compounds from perilla extract on advanced glycation end products (AGEs) - Xue Han; Xue Sun; Zihang Shi; Xiankang Fan; Yangyang Hu; Chen Chen; Qiang Xia; Yangying Sun; Daodong Pan (Food Chemistry: X)
This study investigates the inhibitory effects and underlying mechanisms of major polyphenolic compounds in perilla extract on the formation of advanced glycation end products using a high-temperature in vitro glycation model. Ultra-performance liquid chromatography coupled with mass spectrometry identified quercetin, luteolin, rosmarinic acid, sinapic acid, and other representative bioactive constituents in PE. These polyphenolic compounds significantly inhibited protein-bound Nε-(carboxymethyl)lysine (41.3 % - 61.1 %), mainly through free radical scavenging, metal ion chelation, and suppression of protein aggregation, thereby mitigating protein oxidation and modulating protein conformation. Further mechanistic analysis revealed that these polyphenols regulated protein surface hydrophobicity, altered protein particle size, and influenced intermolecular interactions, thereby impacting the glycation process. Overall, this study elucidates the molecular mechanisms by which polyphenolic compounds inhibit AGEs formation under high-temperature conditions and provides a theoretical basis for the development of effective AGEs inhibition strategies in processed meat products.